Evaluation of transcriptional cyclin dependent kinase inhibitors as potential cancer therapeutics - Liu, Xiangrui (2012)
Cancer cells depend heavily on sustained expression of anti-apoptotic proteins. Targeting transcription to suppress these anti-apoptotic proteins seems a promising strategy for anti-cancer therapy. Cyclin-dependant kinase 9 (CDK9) regulates transcription elongation by phosphorylating Ser2 on the C-terminal domain of RNA polymerase II, while CDK7 phosphorylates Ser5 during transcription initiation. A screening cascade comprised of an MTT assay, a caspase-3 activation assay, a p53 stabilization assay and a mitotic index assay was developed to classify compounds and identify lead transcriptional CDK inhibitors from a novel class of 2,4,5-trisubstituted pyrimidines. Compounds S3-41 and CDKI-71 are the most potent CDK9 inhibitors identified by the screening cascade. They showed potent anti-proliferative activity in the MTT assay and induce both caspase-3 activity and p53 protein level at the GI50 concentration. In addition, no significant effect on mitotic index was observed.